Are All Cancer Stem Cells Created Equal?. (13th August 2014) - Xie, Xiujie; Teknos, Theodoros N.; Pan, Quintin
Summary: Numerous solid malignancies have been reported to contain cancer stem cells (CSCs). Distinct functional characteristics have been attributed to CSCs, and thus it is widely believed that these unique cells may have genetic and phenotypic homogeneity. Recent exciting but limited evidence, however, contradicts this tenet and supports the intriguing concept of genetic and phenotypic diversity in the CSC population. We propose that CSC heterogeneity at the inter- and intrapatient levels may be due to the cell of origin, to environmental cues, and/or to human papillomavirus infection. Additional insight into CSC heterogeneity is needed to identify actionable targets for optimal eradication of the diverse CSC subpopulations within a tumor. Abstract : Recent exciting but limited evidence supports the intriguing concept of genetic and phenotypic diversity in the cancer stem cell (CSC) population. The authors of this paper consider whether CSC heterogeneity at the inter- and intrapatient levels may be due to the cell of origin, to environmental cues, and/or to human papillomavirus infection.